Study on Plagioclase and Origin of Silicic Rock Samples From Þjófadalafjöll - Sigríður María Aðalsteinsdóttir 1993- (2019)
Three silicic igneous rock samples from Þjófadalafjöll confined to Þjófadalafjöll central volcano, near Kjölur in mid-highland of Iceland were analyzed in this thesis. The main goal is to try to determine if they formed by fractional crystallization or partial melting of hydrated basaltic crust, which are the most favored ideas for silicic igneous rock-forming processes in Iceland. Silicic rocks are relatively rare in Iceland and constitute roughly 11%, where intermediate rocks are around 14% and basaltic rocks 75%. Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDS) measurements were taken of plagioclases and groundmass. The overall anorthite content of rhyolite, obsidian and dacite samples were An30-64, An18-60 and An43-74 for the mineral cores. For the rims they were An25-60, An37-40 and An34-59. Almost all of the plagioclase rims are richer in calcium rather than sodium, resulting in more anorthite composition. Approximate groundmass mineral assemblage of these samples according to CIPW norm calculations were 25.5% quartz, 40.5% plagioclase, 23.0% orthoclase, 5.6% diopside, 1.7% hypersthene, 0.7% magnetite and 0.1% apatite for the rhyolite sample, 23.6% quartz, 46.5% plagioclase, 20.7% orthoclase, 5.6% diopside, 2.7% hypersthene, 0.9% magnetite and 0.1% apatite for the obsidian sample interior and 34.9% quartz, 46.4% plagioclase, 12.4% orthoclase, 1.5% hypersthene, 0.5% magnetite and 0.1% apatite for the dacite. This results mostly in higher than 70% SiO2 of the groundmass. Rare earth elements (REE) normalized to Enriched-Mid Ocean Ridge Basalt (E-MORB) and ordinary chondrite showed no steep changes in incompatible elements nor compatible ones. Therefore, it is unlikely that these silicic igneous rocks formed by fractional crystallization. Results lean to rather partial melting processes or even magma mixing, between basaltic and silicic magma.